Limit theorems for sums of random vectors combined into a non-homogeneous Markov chain II - Raudeliūnas, A. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. К. Рауделюнас, Предельные теоремы для сумм случайных векторов, связанных в неоднородную цепь Маркова II A. Raudeliūnas, Ribinės teoremos atsitiktinių vektorių, surištų į nehomogeninę Markovo grandinę, sumoms II